Roles in the Alcoholic Family and Needs Structure of Alcoholics’ Adult Children. - Ryś, Maria; Wódz, Elżbieta (Studia Psychologica: Theoria et praxis, 2003)
The article author presents her own new research method of discovering the roles played by children, currently adult women, in the alcoholic family. According to the author the dysfunctional family is characterized by the frustration of its members’ interactions, abuse of some of its members, violation of fundamental human rights, and lack of responsibility for others in the family. An alcoholic family possesses all of these defects. Also the situation and role of the children and mate in such families are analyzed. Finally, the author discusses the consequences of the alcoholic family for its adult children. The research group consisted of 30 women – adult alcoholics’ children. The selfimage of these persons was defined depending on the role played in childhood.